Crash course in prediction and mitigation for a crashing system: A complex biocultural sociological perspective of sudden social decline - Laurenc L. De Vita (The Central European Review of Economics and Management (CEREM), 2023)
Aim: To present a condensed but inclusive discussion of the nature of the complex global system and the impediments to, but also the advantages of, means of prediction and action in a rapidly declining society to offer a compendium of the potential to assess the difficulty of predicting complex social systems. Research methods: A review and synthesis of research material on: the function of dissipative systems, most specifically the global social system; the means to discern, measure and assess three kinds of energy through functional networks; the intractable difficulties with prediction and agency. Conclusions: Regardless the inherent difficulty in prediction and agency in complex systems, there is a benefit to having some methodology. That is, it is better to understand how the system works, and to be able to identify, if just a short while in advance, what might happen and what responses we might have, and to do that we need to have an organized way to look at things. Originality / value of the article: Offers, to a broad variety of large and small organizations, a brief guide to conceptualizing the global system, its functioning parts and sources of energy, and the imperative and difficulty of predicting and strategizing for changes in a declining system. Implications of the research: There is benefit to a thorough understanding of the complex social system, if it allows prediction and response to system changes. Limitations of the research: It is a "crash course", and ideas are explored but not exhaustively described.
Keywords: D91; E71; H12; 330; complex systems; disaster management